Technology-based factors of globalization in market and transition economies. Is there a difference? - Petkovski, Ivana; Fedajev, Aleksandra; Mihajlović, Ivan (Business, Management and Economics Engineering, 2024)
Purpose – The global crises that emerged during the last two decades proved that economies that focus their development on demand are the most vulnerable during crises. However, development strategies depend on specific internal and external circumstances impacting development of particular country. In that sense, this research aims to identify how digitalization, science and technology, and ICT trade impact globalization in market and transition economies.Research methodology – Authors employed the PLS-SEM methodology on available dataset for 32 European economies.Findings – According to the findings, digitalization is the factor that has the highest positive impact on globalization in market economies, while ICT trade has the greatest positive impact on globalization in transition economies. Science and technological advancements have a diverse impact. The MGA results stressed out the difference between these groups even more clear.Research limitations – The presented model does not consider country-level analysis of globalization.Practical implications – The study is providing theoretical and empirical base for strategy and policy development in the globalization domain in line with economy character.Originality – The value of the research is found in contributing to the globalization topic in market, and particularly in transition economie that lack empirical research in this field.